2020
DOI: 10.1111/ijpp.12667
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric data based on the Pharm.D. and Ph.D. degree in United States research-intensive colleges of pharmacy

Abstract: Objectives The objective of this work was to compare bibliometrics based on doctoral degrees within United States colleges of pharmacy to understand productivity differences. Secondary objectives were to provide quantitative data based on degree that could be utilized by individual faculty, administration and other key stakeholders in academic pharmacy. Methods Bibliometric indices were obtained from Scopus and Web of Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…6 Previous research using bibliometric publication data comparison of PharmD-PhD versus PharmD in US research-intensive colleges of pharmacy showed higher Scopus and Web of Science scores and average citations per publication, respectively. 13 Our data extends these findings to all DPP-TT dual-degree faculty in the United States and Puerto Rico, showing significant differences in journal impact factor and NIH iCite-Weighted RCR supporting that dual-degree faculty are making a difference in health-related human research.…”
Section: Ninetysupporting
confidence: 73%
See 4 more Smart Citations
“…6 Previous research using bibliometric publication data comparison of PharmD-PhD versus PharmD in US research-intensive colleges of pharmacy showed higher Scopus and Web of Science scores and average citations per publication, respectively. 13 Our data extends these findings to all DPP-TT dual-degree faculty in the United States and Puerto Rico, showing significant differences in journal impact factor and NIH iCite-Weighted RCR supporting that dual-degree faculty are making a difference in health-related human research.…”
Section: Ninetysupporting
confidence: 73%
“…Faculty with appointments of adjunct, emeritus, or research positions were excluded. 4 Faculty who had completed a fellowship were not counted as a primary or secondary degree, as they were not deemed to have completed an earned degree. The authors recognize the importance of fellowship training to the profession, 11 but excluded these individuals as fellowships were not consistently listed in faculty listings.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations